An effect of straight and serpentine flow fielddesign on proton exchange membrane fuel cell - Manshoor, Bukhari; Mohamed Ster, Laily Azwati; Khalid, Amir; Zaman, Izzuddin (Asian Research Publishing Network (ARPN), 2017)
Proton exchange membrane fuel cell (PEMFC) is energy conversion device especially in future use in stationary and vehicular applications. PEMFC’s provide high efficiency and power density with null emission, low operating temperature, quickly start and long life. One aspect that is crucial to optimizing the performance of PEM fuel cells understands is the physics in the flow field and how changes in flow field geometry affect the performance. Hence, in the present study, a model of PEM fuel cell was simulated to understand the effect of straight and serpentine flow field on performance of fuel cell and to predict the effects of changes in the flow field geometry. Commercial Computational Fluid Dynamics (CFD) software was used to extend a numerical three dimensional model of a single PEM fuel cell. Numerical model assumed as a steady state, including Navier-Stokes equations, phase equilibrium, governing electrochemical equations and energy equation. These equations resolved in order to get flow channel and gas diffusion media characteristics, the local current density on the membrane surface, velocity along flow channel and the temperature of the entire control volume. The results show that the local velocity distributions become more uniform for straight flow field designs compare to the serpentine flow field designs. The simulation work here also gives a good agreement with the experimental results and gave a high confidence for the results in order to determine the effectiveness of the flow field design in PEMFC.